Urban growth by fragments. Consolidation and land value in peripheral areas resulting from housing policy in Córdoba, Argentina - Marengo, Maria Cecilia (2023)
The study of the consolidation of built-up areas in the periphery of cities is interesting because it is linked to the differential forms of access to land, services, urban facilities, workplaces, and daily mobility for the inhabitants. The research identifies the locations of public housing in Córdoba City and the transformations that were produced in the physical morphology of the surroundings during a decade. Land uses, the level of building consolidation, and the dynamics of land prices in the surrounding areas lead us to reflect on the evolution of social housing areas as urban fragments built on the periphery. The objectives of the study are to recognize the effects of housing policy location in urban development and to discuss the sustainability of the urban growth model. In the context of the increasing commodification of the city, this development pattern intensifies socio-territorial inequalities derived from the location of low-income families in scattered outlying areas.